Measure incl. wooden frame; bronze relief. With text: 'Gewidmet vom Magistrat der Stadt Steinheim a/Main Deutschland'. Probably offered to the 'Stem des Volks'
Measure incl. wooden frame; bronze relief. With text: 'Gewidmet vom Magistrat der Stadt Steinheim a/Main Deutschland'. Probably offered to the 'Stem des Volks'.